UI/UX Development Using Figma based on Inclusive Design - Kimseng, Ngov; Kurnia, Dian Ade; Vuthy, Ith; Arifin, Rita Wahyuni; Setiyadi, Didik (JINAV: Journal of Information and Visualization, 2023)
The existence of User Interface (UI) and User Experience (UX) Designer has been highly increasing and needed in recent times. One of the reasons is that many companies are starting to use Website and Mobile Application all of these actions occurred in a convincing way that attracted users, however, each of them support the objective of business development. In answering this problem, knowledge of UI/UX is needed in terms of conduction for using it. Therefore, needed designer must use several processes in the research method that the author uses, namely empathize, define, ideate, prototype, and test. The purpose for designers, there are many resources to fulfil the lack of education and to prevent working hard, it assists designers in working and creating for all frameworks and inclusive design. Also, the contributes to designers with a practical framework, aligning with industry standards, and fostering a user-centric approach. It ensures digital products are inclusive, promoting diversity, and advancing design in the technology industry. In addition, how a designer can incorporate their unique ideate for building Websites and Mobile Applications. The result of the Design Thinking method in this research is to expertly improve the user’s experience better than before. And the result application was efficient based on the participants rate are successful effective. Satisfying based on overall rate 98.4% after see this and when using the application.